Mobile Cloud And Cloudlets Gaming System (Mccg) Using Clustered Destination-Sequenced Distance Vector Routing Protocol(C-DSDV) - Doraisamy, Vaithegy (2020)
This research work was designed to investigate the effectiveness of enhanced Cloud Mobile Gaming (CMG). The existing MCG system was enhanced by introducing cloudlets and mobile ad hoc network in the system in order to reduce the latency in MCG system. Cloudlets were introduced to reduce the transmission distance between main cloud and mobile users meanwhile mobile ad hoc network was introduced to reduce the service waiting time of the system